Serum uric acid to serum creatinine ratio predicts neurological deterioration in branch atheromatous disease - Liu, Yinglin; Wang, Honglei; Xu, Ronghua; He, Lanying; Wu, Kun; Xu, Yao; Wang, Jian; Xu, Fan (Frontiers in Neurology, 2023)
Background and Objective: Branch atheromatous disease (BAD) makes patients prone to early neurological deterioration (END), resulting in poor prognosis. The aim of this study was to investigate the association between SUA/SCr and END in BAD stroke patients. Methods: We conducted a retrospective study that included 241 patients with BAD-stroke within 48 h of symptom onset. We divided the patients into the END group and the no END group. END was defined as an NIHSS score increase of more than 2 points within 1 week. SUA/SCr was calculated by the concentration of serum uric acid and creatine (serum uric acid/serum creatine) on admission. Univariate and multivariate analyses were used to identify independent predictors of END in BAD-stroke patients. Results: END was observed in 24.1% (58/241) of the patients in our study. Multiple logistic regression analyses showed that SUA/SCr (aOR, 0.716; 95% CI, 0.538-0.952; P=0.022) and female sex (aOR, 0.469; 95% CI, 0.245-0.898; P=0.022) were ssociated with END after adjusting for confounding factors. The predicted value of SUA/Scr for END was a sensitivity of 79.3%, a specificity of 44.8%, and an AUC of 0.609 (95% CI, 0.527–0.691, P<0.05). The optimal cut-off value was 4.76. Conclusion: SUA/SCr was negatively associated with the risk of END in BAD stroke patients.